Endoscopic Resection of a Rare Case of Frontoethmoidal Glomangiopericytoma: A Case Report - Costa Gomes, Sara; Machado da Silva, Eduardo Oliveira (ENT Updates, 2024)
We report a case of a 58-year-old man with a history of nasal obstruction and recurrent epistaxis who underwent videonasolaryngoscopy after 9 months of symptoms. The frst images showed a hyperemic mass affecting the left middle turbinate up to the nasal cleft. Computed tomography described a mass with an expansive effect occupying the entire left frontal sinus and most of the left ethmoid cells, widening the frontal sinus drainage path, and creating a continuity break of the cribriform plate, the left papyraceous lamina, and the upper-third of the nasal septum. Magnetic resonance imaging suggested T1-isointensity and T2-hyperintensity, intense contrast uptake, and no involvement of meningeal or brain tissues. The patient underwent extended endoscopic surgery without previous endovascular embolization or adjuvant therapies. A contralateral inferior turbinate graft was applied over the cribriform plate. Histopathological examination suggested glomangiopericytoma (GPC), and immunohistochemistry confrmed the diagnosis with positive beta-catenin, smooth muscle actin, and cyclin D1. The patient presented no nasal symptoms up to a 9-month follow-up. Nasal endoscopy showed no tumor recurrence signal. Although fronto-ethmoidal GPC is a rare tumor and presents challenging surgical access, it can be safely excised by endoscopic surgery. However, careful short- and long-term endoscopic follow-ups remain necessary to prevent postoperative complications and maintain surveillance of recurrences.